Recent developments in the Finnish banking sector - Atso Andersén; Ari Hyytinen; Jussi Snellman (Bank of Finland, 2000)
In this paper we discuss recent developments in the Finnish banking sector.Our specific aim is to examine whether and to what extent recent developments in Finland are broadly in line with the trends common to banking sectors in Europe and also worldwide. We focus on developments in banks' profit and loss accounts, balance sheets and the market structure of the banking sector.In addition, technological developments are surveyed.As regards consolidation, the Finnish banking sector is a trendsetter.The emphasis in structural development has moved to cross-border banking and bankassurance.On the other hand, it turns out that it is quite hard to track some of the trends that are believed to characterize European banking sectors using Finnish data.For instance, disintermediation has thus far been moderate in Finland, as the role of banks as providers of financing to households and companies is still significant and generally shows no signs of diminishing.Tougher competition in lending does not seem to have reduced Finnish banks' profitability, which was at a record high in 1999 and in the first half of 2000. The Finnish banks have fully recovered from the banking crisis of the early 1990s.Improved profitability is largely due to enhanced efficiency as well as recent favourable economic performance.The banking sector has experienced a rapid process of consolidation during the 1990s and currently banks are in the middle of a period of intensive launching of new technology-based products.It can be argued that as a result of developments in the 1990s, the Finnish banking sector is among the most profitable and efficient in Europe.
URN:NBN:fi:bof-20140807556
Keywords: 330; Banks; financial system; stability